Learning PHP, MySQL & JavaScript with jQuery, CSS & HTML5 - Nixon, Robin (O'Reilly Media, 2015)
Build interactive, data-driven websites with the potent combination of open-source technologies and web standards, even if you only have basic HTML knowledge. At the end of the book, you'll put everything together to build a fully functional social networking site, using XAMPP or any development stack of your choice.